The urological management of children with spinal dysraphism - Jee, Larry Donald (Division of Urology, 2017)
This project was undertaken with the following aims: 1) To generate a data base concerning the management of children with congenital spinal anomalies, who are known to form a significant proportion of the patients being treated in the Department of Paediatric Urology at Red Cross Hospital. 2) To assess the results of the management of these children, with special attention to the goals of therapy, namely preservation of renal function, establishment of urinary continence and protection from urinary tract infection. 3) To compare the treatment methods and results obtained to those reported in the literature. 4) To evaluate critically the treatment methods and results obtained with a view to identifying areas where improvements are possible.